Boys versus girls: gendered presentations of newborns via Instagram photograph uploads - Garcia, Jason (My University, 2016)
The present study examined the prevalence of gender stereotypes displayed in photograph uploads of newborns in the mobile social media application, Instagram. A quantitative content analysis was performed on a sample of 120 of the most recent photograph uploads with the hashtag streams “#newbornbabyboy” and “#newbornbabygirl”. 60 of these images consisting of each newborn females and males, collected between the 26th and 27th of March, 2014. Results showed that newborn baby boys were only portrayed in a gender-stereotypical manner where the most predominant clothing colour worn was blue. For girls, the results also revealed a gender-stereotypical pattern as pink was the most displayed clothing colour. There was no significant difference found between male and female newborns in how often they were accessorized. The primary source of the photograph uploads were most often the babies’ mothers.
Keywords: gender; stereotypes